The Study of Poems of Abdulla Avlani in Primary Classes - (IJIE), International Journal on Integrated Education (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
In this article, Abdulla Avlani's views on the development of modern science as a great thinker, scientist and educator as a harmonious person, as well as the importance of modern science in their time, are currently emphasized to study such importance, pedagogical views of a mature teacher and to pay attention to its role and actual importance in the education of today's.